Case Studies Using the Electroencephalogram to Monitor Anesthesia-Induced Brain States in Children - Brandt, Steven P. (Anesth Analg, 2020)
For this child, at this particular moment, how much anesthesia should I give? Determining the drug requirements of a specific patient is a fundamental problem in medicine. Our current approach uses population-based pharmacological models to establish dosing. However, individual patients, and children in particular, may respond to drugs differently. In anesthesiology, we have the advantage that we can monitor our patients in real time and titrate drugs to the desired effect. Examples include blood pressure management or muscle relaxation. Although the brain is the primary site of action for sedative-hypnotic drugs, the brain is not routinely monitored during general anesthesia or sedation, a fact that would surprise many patients. One reason for this is that, until recently, physiologically principled approaches for anesthetic brain monitoring have not been articulated. In the past few years, our knowledge of anesthetic brain mechanisms has developed rapidly. We now know that anesthetic drug effects are clearly visible in the electroencephalogram (EEG) of adults and reflect underlying anesthetic pharmacology and brain mechanisms. Most recently, similar effects have been characterized in children. In this article, we describe how EEG monitoring could be used to guide anesthetic management in pediatric patients. We review previous evidence and present multiple case studies showing how drug-specific and dose-dependent EEG signatures seen in adults are visible in children and infants, including those with neurological disorders. We propose that the EEG can be used in the anesthetic care of children to enable anesthesiologists to better assess the drug requirements of individual patients in real time and improve patient safety and experience.